Rethinking Terror and Horror with Plato, Aristotle, and Shakespeare - Mydla, Jacek (Zagadnienia Rodzajów Literackich, 2025)
This article addresses a blank spot in Gothic studies and in studies of ways in which literature purveys terror, horror, and fear. In the last decades, Gothic studies, including Jacek Mydla’s book, have broadened their scope of research by including Shakespeare’s influence on Gothic romance and drama in eighteenth-century England. Shakespeare’s handling of the ghosts in Hamlet and Macbeth offered Gothicists artistic models of handling terror, especially its supernatural variety: the ghost. While such research on the Gothic broadens our understanding of the genre’s development in its historical and cultural context, it fails to place terror within a comprehensive ethic. Edmund Burke’s theory of the sublime is notoriously deficient in this respect, similarly to an aesthetic that conceives terror as mind-expanding or merely entertaining. Pursuing Horace Walpole’s reference, in the preface to the first edition of The Castle of Otranto, to the cathartic emotions of terror and pity, Mydla explores two interrelated contexts: Plato’s critique of Homer’s representations of terrors of death and the after-life and Plato’s fashioning of Socrates as a philosophical role model in opposition to the impassioned heroism of Achilles. Mydla argues that such “ancient” recontextualising, where Plato’s critique and Aristotle’s insights are related to lessons from Shakespeare’s handling of terror and horror in Hamlet, has the potential to enrich contemporary critical reflection.